Pengaruh Kualitas Layanan dan Keterlibatan Mahasiswa terhadap Kepuasan Mahasiswa pada Jurusan Akuntansi Di Surabaya - Felicia Lisady; Felicia Wong; Sany Sany (Business Accounting Review, 2021)
Online learning is currently being carried out thoroughly in order to reduce interaction between students and lecturers in order to minimize the impact of the transmission of the COVID-19 virus. In such a learning experience, it is believed that contact between lecturers and students will encourage students to be involved in ongoing learning, so as not to reduce the quality of the learning process. Student satisfaction is an evaluation that the quality of information or knowledge meets student expectations. This study aims to examine the effect of service quality and student involvement on student satisfaction. The variables in this study were measured using a questionnaire adopted from previous studies. This research is focused on accounting students at universities in East Java, Indonesia, especially students from the 2018-2021 class at three universities. A survey was distributed online and has collected 323 valid respondents. Partial Least Squares (PLS) method was used to evaluate the hypothesis in this study. This study found that there is a positive and significant relationship between service quality and student engagement on student satisfaction.